2008
DOI: 10.2174/157340408783572033
|View full text |Cite
|
Sign up to set email alerts
|

Menopause, A Universal Female Experience: Lessons from Mexico and Central America

Abstract: In Mexico and Central America, women typically experience menopause up to 10 years earlier than their U.S. counterparts. This may be due in part to numerous pregnancies, long periods of lactation, poor nutrition, extreme environment, and the heavy workload of the Maya women. Unlike Western culture, there is no stigma associated with aging and the menopausal period in the Mayan culture. In fact, menopause is considered to be a welcome natural phenomenon in Central America that all Maya women, who come of age, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…The MT includes three stages— Early Menopause Transition , Late Menopause Transition , and Early Postmenopause —each of which is distinguished by progressive irregularity and eventual cessation of the menstrual cycle, outlined in detail elsewhere in this paper. Many physical and psychosocial symptoms can accompany this transition, the severity of which disrupts women’s quality of life (QOL) to varying degrees [2, 3]. A 2016 study revealed that of a representative sample of 3397 US women with an age range of 40–69 years, 52% would always prefer a reduced lifespan to experiencing menopausal symptoms at their worst for 30 days [4].…”
Section: Introductionmentioning
confidence: 99%
“…The MT includes three stages— Early Menopause Transition , Late Menopause Transition , and Early Postmenopause —each of which is distinguished by progressive irregularity and eventual cessation of the menstrual cycle, outlined in detail elsewhere in this paper. Many physical and psychosocial symptoms can accompany this transition, the severity of which disrupts women’s quality of life (QOL) to varying degrees [2, 3]. A 2016 study revealed that of a representative sample of 3397 US women with an age range of 40–69 years, 52% would always prefer a reduced lifespan to experiencing menopausal symptoms at their worst for 30 days [4].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on their geographical location within Mexico, it is estimated that between 12 to 60% of Mexican women depend on MTM practices and herbal medicines for their primary healthcare needs 8,51,[65][66][67][68]70,71,[79][80][81][82][83] . The use of MTM is more prevalent in rural areas where access to modern clinics and healthcare is limited, especially during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…The IMSS and the Mexican Ministry of Health and Welfare operate most of the healthcare clinics, and the lack of staffing of community healthcare workers and physicians, may make the quality of care inconsistent, and not culturally sensitive 79 . Language is also an important aspect of healthcare, and since many Western trained health workers do not speak indigenous languages, indigenous women often have difficulty explaining their symptoms 66,67,83 . Many Mexican women prefer MTM healers, as well as birthing services offered by midwives rather than nurses and doctors, because midwives incorporate traditional beliefs and medicinal plants into their work, thus preserving the connection with their culture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Menopause, also known as the climacteric, is defined as the cessation of menstruation for successive 12 months (Mahady et al, 2008). Menopause syndrome can lead to uncomfortable symptoms of hot flushes, psychological symptoms, as well as reproductive tract complications such as vaginal dryness and loss of libido (Al‐Azzawi, 2001).…”
Section: Introductionmentioning
confidence: 99%